Sulfur-locked multiple resonance emitters for high performance orange-red/deep-red OLEDs - Yexuan Pu; Qian Jin; Yuewei Zhang; Chenglong Li; Lian Duan; Yue Wang (Nature Communications)
Abstract Multiple resonance thermally activated delayed fluorescence (MR-TADF) materials are preferred for their high efficiency and high colour purity in organic light-emitting diodes (OLEDs). However, the design strategies of MR-TADF emitters in the red region are very limited. Herein, we propose a concept for a paradigm shift in orange-red/deep-red MR emitters by linking the outer phenyl groups in a classical MR framework through intramolecular sulfur (S) locks. Endowed with the planar architectural feature of the MR mother core, the proof-of-concept S-embedded emitters S-BN and 2S-BN also exhibit considerable flatness, which proves critical in avoiding the direct establishment of potent charge transfer states and inhibiting the non-radiative decay process. The emission maxima of S-BN and 2S-BN are 594 nm and 671 nm, respectively, and both have a high photoluminescence quantum yield of ~100%, a rapid radiative decay rate of around 107 s−1, and a remarkably high reverse intersystem crossing rates of about 105 s−1. Notably, maximum external quantum efficiencies of 39.9% (S-BN, orange-red) and 29.3% (2S-BN, deep-red) were also achieved in typical planar OLED structures with ameliorated efficiency roll-offs.